Corrigendum : Effectors by outer membrane vesicles in Salmonella enterica serovar Typhimurium (Frontiers in Microbiology (2018) 9 (2810) DOI: 10.3389/fmicb.2018.02810) - Kim, Seul I.; Kim, Seongok; Kim, Eunsuk; Hwang, Seo Yeon; Yoon, Hyunjin (Frontiers in Microbiology, 2019)
In the original article, there was a mistake in Table S2 as published. Some primers listed in Table S2 had incorrect sequences. The corrected Table S2 appears below. [Table Presented]. The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.